Hubungan Antara Tingkat Pengetahuan tentang Cyberbullying dan Intensitas Penggunaan Media Sosial Instagram dengan Tingkat Perilaku Cyberbullying di Media Sosial Instagram - Fani Adhiti; Triyono Lukmantoro; Wiwid Noor Rakhmad (Interaksi Online, 2023)
The majority of modern communication is almost completely relying on digital technology, which if not handled carefully can promote destructive behavior. Cyberbullying is one such destructive behavior. Cyberbullying is more prevalent on Instagram, which is thought to be caused by the availability of mobile devices and inexpensive internet connections. As a result, an increasing number of users are accessing Instagram without having a thorough understanding of cyberbullying. This study aims to investigate the relationship between knowledge levels of cyberbullying and Instagram usage intensity to cyberbullying levels on Instagram through communication theory verification of Knowledge-AttitudeBehavior (KAB) Model, Problem Behavior Theory, and Social-Cognitive Theory. This explanatory research uses non-probability sampling and purposive sampling techniques to analyze quantitative data. 100 young adults in Pati Regency, aged 18 to 34, who actively use Instagram and have seen cyberbullying-related content on the platform were utilized as a sample for this study. Kendall's Tau-b and Kendall's W correlation tests were used to assess hypotheses. The findings demonstrated that knowledge levels of cyberbullying had no relationship when tested partially to cyberbullying levels on Instagram. Similar results also occur for Instagram usage intensity when tested partially to cyberbullying levels on Instagram. However, knowledge levels of cyberbullying and Instagram usage intensity actually showed a relationship when tested simultaneously to cyberbullying levels on Instagram, but there are some considerations to keep in mind.